The Impact of Distance Learning on Time Management among Students in Poland in the Era of COVID-19 - Michał OLEJNICZAK; Joanna URBAN; Krzysztof KICZEK; Aleksander SZYMICHOWSKI (Communications of International Proceedings, 2023)
This paper fills a gap in the literature. This work aims to answer the question: How does the issue of time management among students in Poland look like in a dynamically changing world? The COVID-19 pandemic meant that academic classes in Poland switched to online mode. Due to the change in the way of conducting classes, students have additional time. 614 students from various universities in Poland participated in the survey. The basis of the conducted research was the formulation of the following hypotheses: Distance learning resulted in more free time. Online teaching inhibits scientific development - it reduces efficiency and negatively affects self-development motivation. Online learning contributed to the formation of academic apathy among the respondents. Online learning has increased interest in work at the expense of devoting time to education. The results of the research showed that, on the one hand, students had extra time (they did not have to commute to the university), and on the other hand, their involvement in learning decreased. This opens the way to searching for the reasons for this state of affairs. The fault lies not only with the students but also with the need for systemic solutions and the unpreparedness of lecturers for online teaching.
Keywords: Covid-19 pandemic; remote work; time management; students; distance learning